2017
DOI: 10.1111/phpp.12294
|View full text |Cite
|
Sign up to set email alerts
|

23‐Hydroxytormentic acid protects human dermal fibroblasts by attenuating UVA‐induced oxidative stress

Abstract: In conclusion, 23-HTA protects against and attenuates UVA-induced oxidative stress in NHDFs likely via the nuclear factor erythroid-derived 2-like 2 signaling pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…Therefore, the inhibition of ROS production and lysosome contents was due to the ability of ES-GNPs to reduce HDF senescence by stimulating UVA irradiation. Senescence related proteins including p16, p21 and p-p53 have also been proposed to play a critical role in UVA-irradiated HDF senescence [4]. In our study, we found that treatment with ES-GNPs inhibited the expression level of p16, p21 and p-p53, indicating the dependence of p16, p21 and p-p53 in ES-GNP-initiated anticellular senescence effects.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…Therefore, the inhibition of ROS production and lysosome contents was due to the ability of ES-GNPs to reduce HDF senescence by stimulating UVA irradiation. Senescence related proteins including p16, p21 and p-p53 have also been proposed to play a critical role in UVA-irradiated HDF senescence [4]. In our study, we found that treatment with ES-GNPs inhibited the expression level of p16, p21 and p-p53, indicating the dependence of p16, p21 and p-p53 in ES-GNP-initiated anticellular senescence effects.…”
Section: Discussionsupporting
confidence: 58%
“…A hypothetical hydrolase, e.g., SA-β-galactosidase, is commonly used as an indirect essential maker of senescent cells. There is evidence showing that the HDF senescence caused by UVA irradiation could cause the increase of SA-β-galactosidase activity [4]. In our study, UVA irradiation caused an increase in SA-β-galactosidase activity in HDF, while intervention with ES-GNPs noticeably diminished the impact thereof.…”
Section: Discussionsupporting
confidence: 44%
See 2 more Smart Citations
“…Long-term UVR irradiation causes skin damage, leading to skin photoaging, and the main damage is in the dermis, which is also the main area for repairing skin trauma [18]. UVA can penetrate the dermal layer of the skin [19]. So, it is worth mentioning that UVA mainly influences the human papillary dermis fibroblasts.…”
Section: Discussionmentioning
confidence: 99%